Dukungan Suami Berhubungan Dengan Ketercapaian Asi Eklsusif - Putriana, Yeyen; Risneni, Risneni (MIDWIFERY JOURNAL, 2022)
Background :Breastfeeding is a natural and lengthy process compared to childbirth. Breastfeeding has many factors that support its success during the period of exclusive breastfeeding and 2 years. The failure of exclusive breastfeeding is mostly caused by the mother's lack of knowledge and the absence of family support, especially husbands and in-laws or biological mothers. It is not yet known how the husband's support affects the achievement of exclusive breastfeeding for 6 months. Purpose: This study aims to determine the relationship of husband's support for breastfeeding mothers to the achievement of exclusive breastfeeding in 6 months.Method: The study used a quasi eksperimen research design. The research will be conducted at Kemiling Public Health Center Bandar Lampung in september 2021. The research subjects are breastfeeding mothers with babies aged 6-12 months. The sample size uses the purposive sampling formula. Data analysis used bivariate analysis with Spearman correlation test.Results: the prevalence of exclusive breastfeeding is 30%. Most husbands support exclusive giving (80%) compared to husbands who do not support (20%). Spearmen correlation test results show that there is no significant relationship between support and exclusive breastfeeding. Conclusions :Mothers who received support from their husbands had a greater proportion of exclusive breastfeeding compared to those who did not receive support, although there was no statistically significant relationshipSuuggestion : it is necessary to have a group of fathers who support breastfeeding to provide moral and emotional technical information support Keywordd : exlusive breastfeeding, husband suport ABSTRAK Latar belakang : Menyusui adalah proses alami dan lama dibandingkan dengan proses persalinan. Menyusui mempunyai banyak factor yang menunjang keberhasilannya selama periode asi eklusif dan 2 tahun.  Kegagalan ASI ekslusif banyak disebabkan oleh kurangnya pengetahuan ibu dan tidak ada adanya dukungan keluarga terutama suami dan mertua atau ibu kandung. Belum diketahui bagaimanakah pengaruh dukungan suami dengan capaian asi eklusif selama 6 bulan .Tujuan : Penelitian ini bertujuan untuk mengetahui hubungan dukungan suami terhadap ibu menyusui terhadap capaian  asi esklusif dalam 6 bulan .Metode : Penelitian menggunakan rancangan penelitian cross sectinal. Penelitian dilaksanakan di puskesmas Kemiling Bandar Lampung pada bulan februari 2022. Subyek penelitian adalah ibu  menyusui dengan usia bayi 6. Besar sampel menggunakan rumus purposive sampling. Analisa data menggunakan analisa secara bivariat dengan uji korelasi Spearman.Hasil:  penelitian mendapatkan  sebagian besar suami mendukung pemberian si eklusif (80%) dibandingkan dengan suami yang tidak mendukung (20%). Hasil ujikorelasi spearmen menunjukkan tidak terdapat hubungan yang signifikan antara dukungan dengan pemberian asi eklusif.Kesimpulan : Ibu yang mendapat dukungan dari suami memiliki proporsi yang lebih besar memberi asi eklusif dibandingkan dengan tidak mendapatan dukungan  meskipun secara statistik tidak hubungan secara signifikan.Saran : perlu dibentuk kelompok ayah pendukung asi guna memberikan imformasi, tehnik, moral maupun emosional Kata kunci : asi ekslusif,  dukungan suami.